Dynamic and Transient Shear Start‐Up Flow Experiments for Analyzing Nanoclay Localization in PP/PET Blends: Correlation with Microstructure. Issue 1 (24th April 2012) - Entezam, Mehdi; Khonakdar, Hossein Ali; Yousefi, Ali Akbar; Jafari, Seyed Hassan; Wagenknecht, Udo; Heinrich, Gert
Abstract Dynamic and transient shear start‐up flow experiments along with TEM, WAXS, and SEM analyses are performed on PP/PET blends and nanocomposites. The TEM results along with a theoretical analysis based on a thermodynamic model reveal that the clay particles are mainly localized in the PET phase. The localization of nanoclay in PET as the matrix phase leads to a refinement of morphology. The localization of clay is also studied by analyzing changes in complex viscosity and storage modulus in oscillation mode as well as the changes in power law index obtained from steady‐state and transient shear start‐up flow experiments. The changes in the rheological behavior of the blends are attributed to formation of clay network‐like structures.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>